The Use of Artificial Intelligence (AI) in the Development of Library Services: Development of digital reference materials and automation of circulation - Winarto, Cleodora Fitriana (Maliki Interdisciplinary Journal, 2026)
The shift in academic library operations from traditional to digital methods presents complex challenges, particularly regarding the effectiveness of reference services and circulation efficiency. Key issues include reduced direct interaction between librarians and patrons, high administrative burdens, and limited human resources and infrastructure to meet the demands of the digital era. This study uses a qualitative literature review approach to explore the use of Artificial Intelligence (AI) as a solution to these issues. The findings indicate that AI technology, through chatbots, recommendation systems, Natural Language Processing (NLP), and RFID integration, can provide interactive, personalized, and sustainable digital reference services, while accelerating and improving the accuracy of circulation automation. Recommended solutions include improving librarians’ digital literacy, strengthening data protection policies, and building inclusive infrastructure to ensure equitable AI implementation across various types of libraries. In conclusion, AI does not replace the role of librarians, but rather strengthens the transformation of academic libraries into smart libraries that are responsive, efficient, and user-oriented in the digital era.